1998
DOI: 10.1111/j.1834-7819.1998.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuraligia. A retrospective survey of a sample of patients in singapore and Malaysia

Abstract: This survey was undertaken to study the clinical features of trigeminal neuralgia in an Asian population. Demographic data of 44 patients treated at the Dental Faculty of the National University of Singapore and at the University of Malaya were reviewed. The results of the survey were analysed and comparisons made with those of Caucasian patients as reported in other studies where there was a general similarity in the clinical findings. Trigeminal neuralgia presented predominantly in females. Right-sided invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
63
4
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(89 citation statements)
references
References 7 publications
21
63
4
1
Order By: Relevance
“…Other reviewers have reported similar findings (5, 9, 16, 17). The present study showed that the ratio of males to females suffering from TN was 1:2, which is consistent with the results of Loh et al (18) and Shah et al (8) All these previous studies have reported that the peak age of onset is between the fifth and eighth decades of life (12,13,16,17,19,20). This trend was also seen in the current study, with the observed peak age being between the sixth and seventh decades of life.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Other reviewers have reported similar findings (5, 9, 16, 17). The present study showed that the ratio of males to females suffering from TN was 1:2, which is consistent with the results of Loh et al (18) and Shah et al (8) All these previous studies have reported that the peak age of onset is between the fifth and eighth decades of life (12,13,16,17,19,20). This trend was also seen in the current study, with the observed peak age being between the sixth and seventh decades of life.…”
Section: Discussionsupporting
confidence: 82%
“…These results were surprisingly the same as those from a previous study by Shah et al (8). Most of the published studies have revealed that the mandibular division (V3) was most commonly involved and that the ophthalmic division (V1) was less commonly presented (5,7,(9)(10)(11)(12)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Further, all support the typical feature of this condition in which the mandibular and maxillary (V2) divisions are more commonly involved than the ophthalmic.…”
Section: Discussionmentioning
confidence: 56%
“…This concurrence supports the cardinal rule of subjecting patients under 40 years of age who complain of neuralgia-like pain in their face, to a detailed neurological assessment, to exclude associated diseases such as multiple sclerosis (3,5,6). Reviewing the literature, some reports demonstrated a male predominance (1,5,6) while others showed a predominance of females at various ratios (2,7,8). The right side of the face is the most commonly effected due to the narrower foramina rotundum and ovale (7,9).…”
Section: Dear Editormentioning
confidence: 54%
“…6-9 Loh et al 10 stated on his study that this concurrence supports the cardinal rule of subjecting patients under 40 years of age who complain of neuralgia-like pain in the face to a detailed neurological assessment to exclude associated diseases like multiple sclerosis. The causes of trigeminal neuralgia include mechanical suppression by blood vessels, arterial venous malformations surrounding, suppression by lesions or tumors, multiple sclerosis, physical damage of the trigeminal nerve due to surgery or infection, and other unknown factors.…”
Section: Discussionmentioning
confidence: 85%
“…Those triggering stimulus were also reported in the previous study. 10 Neto et al 11 stated that in trigeminal neuralgia the right side of the face usually afflict more than the left, since it is known that the foramen rotundum and foramen ovale on the right is narrower. In this study, the right side of the face was also much more involved (ratio 1.7:1).…”
Section: Discussionmentioning
confidence: 99%